ARGUMENT SCHEMATIC PATTERNS IN EXPOSITORY TEXT WRITING FOR HIGH SCHOOL STUDENTS - Gay, Masayu; Suyono, Suyono; Suwignyo, Heri; Harsiati, Titik (IJIET (International Journal of Indonesian Education and Teaching), 2025)
Writing arguments is a form of patterns and schemata that students have. Therefore, it is important to explore it comprehensively, so that this research aims to reveal argument schemata patterns, both basic and complex patterns, as well as their linguistic features. Through a qualitative approach with schemata theory and Toulmin argument patterns, the research produced three patterns, namely the basic pattern C-G 31 data (27.43), the simple pattern C-G-W 21 data (18.58), and the complex pattern C-G-W-B 10 data (8.85), C-G-W-B-Q 12 data (10.62), C-G-W-B-Q-R 7 data (6.20), C-G-Q 8 data (7.08), C-G-W-Q 11 data (9.73), C-G-B 7 data (6.20), and C-G-W-R 6 data patterns (5.31). Basic patterns are composed of two elements, simple patterns of three elements, and complex patterns are formed beyond the basic and straightforward. Students assert the definition using the linguistic schemata "is" as a claim and describe the object using the linguistic feature "is" in the claim to bolster the argument and serve as a warrant. Reaffirmation through the use of linguistic features, such as "my conclusion," "therefore," "so," "which," "even," and "must," as protection. In summary, three types of student argument schemata are present in the composition of expository texts: basic patterns, simple patterns, and complex patterns.